Learning styles and academic performance in Distance Education: a research in specialization courses - Mendes da Silva, Denise; Araujo Leal, Edvalda; Moura Pereira, Janser; Dutra de Oliveira Neto, José (Review of Business Management, 2015)
Objective – The objective of the study is to identify whether learning styles impact academic performance and online and face-to-face assessment activities in Distance Education. Design/methodology/approach – Learning styles were mapped using the Index of Learning Styles (ILS) of Felder and Soloman (1991). For data analysis, generalized linear models methodology was adopted; the Wald test was used to evaluate the effect of the factors. Theoretical foundation - This research is based on cognitive theory. The model of Felder and Silverman (1988) underlies the ILS of Felder and Soloman (1991), which classifies learning styles into four dimensions: Active / Reflective; Sensory / Intuitive; Visual / Verbal; Sequential / Global. Findings – (i) The predominant profile of the sample consists of the following styles: active, sensory, verbal and sequential; (ii) learning styles impacted academic performance only in the Active / Reflective dimension; (iii) significant differences were found between the mean of online and face-to-face assessment activities only in the Sensory / Intuitive dimension; (iv) the means of online assessment activities are larger in every styles dimensions. Practical implications – Contributions for: (i) professors, as to how to choose and shape teaching strategies, i.e, to adopt teaching techniques that are appropriate to students’ characteristics; (ii) for students, knowing their learning style is important to understand and develop new learning strategies; (iii) educational managers, who can use knowledge about learning styles to structure the LMS with better use of resources and promoting student learning.